The relations of basic and dark personality traits with prosocial tendencies: Exploring gender differences - Wertag, Anja; Ribar, Maja; Bratko, Denis (Psihološka istraživanja, 2018)
Prosocial behavior covers a broad range of actions that are intended to benefit others rather than oneself, forming different types of prosocial tendencies which are linked to different individual characteristics. Moreover, there are some gender differences in types of prosocial behavior that males and females engage in. Therefore, the aim of this study was to investigate personality traits associated with different forms of prosocial tendencies, and whether there are gender differences in these relations. Data were collected on-line on a total of 905 participants (81% female; Mage = 24.30, SD = 6.52) using Prosocial Tendencies Measure (assessing 6 types of prosocial tendencies: altruistic, compliant, emotional, dire, public, and anonymous), Ten Item Personality Inventory, and Short Dark Triad. Results of hierarchical regression analyses (with the basic personality traits entered in the first and the dark personality traits in the second step) indicated that, although the percentage of explained variance in all types of prosocial tendencies was modest (up to total of 24%), the basic personality traits contributed more to explanation of public prosocial tendencies in males than in females. The dark traits had a (negative) contribution to explanation of altruistic prosocial tendencies in both males and females, and a contribution above the basic traits in explanation of emotional, dire and compliant prosocial tendencies only in females. Generally, results showed some interesting patterns, highlighting gender differences in relations of personality traits and prosocial tendencies.
Keywords: personality; Dark Triad; hierarchical regression analysis; prosocial tendencies; personality traits; gender differences